DETERMINATION OF RATIONAL PARAMETERS OF PROSPECTING DRILLING IN ALA VERDI AND ARMANIS DEPOSITS (Proceedings of the YSU C: Geological and Geographical Sciences, 2005)
The questions of optimization of column prospecting drilling on vein type deposit are considered. By researches it's established the rational parameters of drilling different categories, specific axial loading, mechanical speeds, the quantity of irrigative liquid, the increase of wear resistance of diamond crown.